2018
DOI: 10.1007/s11060-018-03002-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with mortality within three months after radiosurgery of asymptomatic brain metastases from non-small cell lung cancer

Abstract: Purpose Routine brain MRI surveillance frequently diagnoses small, asymptomatic brain metastases from non-small cell lung cancer (NSCLC) that are effectively treated with stereotactic radiosurgery (SRS). A subset of patients, however, may die prior to the onset of symptoms. This study identifies clinical features that distinguish neurologically-asymptomatic NSCLC brain metastases patients that die prior to routine 3 month follow-up after SRS. Methods Retrospective chart review from 2007 to 2017 identified 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(37 reference statements)
1
2
1
Order By: Relevance
“…Old age, rapid-type primary tumor, and KPS were found to be insignificant predictors of 90-day mortality in this study [25][26][27][28][29][30]. These results were different from other studies, which might be caused by our shorter time frame of mortality and different pathologic fractures, specifically targeting appendicular bones, instead of spinal metastases.…”
Section: Discussioncontrasting
confidence: 93%
“…Old age, rapid-type primary tumor, and KPS were found to be insignificant predictors of 90-day mortality in this study [25][26][27][28][29][30]. These results were different from other studies, which might be caused by our shorter time frame of mortality and different pathologic fractures, specifically targeting appendicular bones, instead of spinal metastases.…”
Section: Discussioncontrasting
confidence: 93%
“…Overall, SRS was associated with a 22-25% risk of early death. This is similar to a previously published series of surgical patients (23% risk of early death) 15 and slightly higher than a recent retrospective study of SRS (19-23% risk), 16,17 probably due to the inclusion of more high-risk patients in our series. Bennett et al 16 reported an increase in risk of death within three months with additional factors from 5% in the most favorable group to 39% in the unfavorable group.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of the lung cancer patients are diagnosed with advanced stage disease, most with stage IV cancer. More than 90% of lung cancer deaths are attributed directly to the metastatic disease and include those brain metastases ( Ali et al, 2013 ; Kakusa et al, 2018 ). Cigarette smoking is a major risk factor for lung cancer ( Lee et al, 2012 ), and our previous study showed a negative impact of smoking on lung cancer brain metastasis ( Shenker et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%